A Simple Benchmark to Evaluate the Influence Parameters of the Microstructure of the Masonry Wall on Capillary Water Migration Dynamic - Martial Nde Ngnihamye; Fabien Kenmogne; André Abanda; Michel Mbessa; Jean-De-La-Croix Gnappoun; Didier Fokwa (Advances in Civil Engineering)
The effects of masonry wall parameters on the water’s migration are deeply explored via the experimental laboratory simulation method. At this end, an experimental device consisting of a water tank in which a masonry block wall has a contact of around one centimeter with the water at its base is designed. The variation of the compactness of masonry blocks is obtained by compacting the concrete blocks with a hydraulic block press. The investigations consist of the monitoring of moisture front and moisture rate as a function of porosity, obtained by varying the compactness of the masonry wall, and the granular class of sand constituting the masonry. The determination of the granular sand classes was made from the NF P 18-101 standard. Three granular classes of sand were obtained using sand from the Logbadjeck quarry: 0/0.315 mm, 0.63/1.25 mm, and 2.5/5 mm. The obtained results show that the device is a good tool for the experimental analysis of the behavior of different masonry walls under water migration, which are in agreement with existing models in the literature.